Pengaruh Penerapan Model Pembelajaran Game Based Learning Terhadap Minat Belajar PAK Siswa Kelas IX SMP Negeri 4 Doloksanggul Kabupaten Humbang Hasundutan Tahun Pembelajaran 2024/2025 - Novita Romaito Sinaga; Risden Anakampun; Sabar Rudi Sitompul; Damayanti Nababan; Ronny Simatupang (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Sinaga, Novita Romaito. 2024. "The Influence of PAK Learning Interest Through the Implementation of the Game Based Learning Model for Class IX of SMP Negeri 4 Doloksanggul, Humbang Hasundutan Regency, Academic Year 2024/2025." Thesis: Christian Religious Education Study Program, Tarutung State Christian Institute. The aim of this research is to determine the positive and significant influence of Game Based Learning by PAK teachers on the interest in learning PAK of class IX students of SMP N 4 Doloksanggul for the 2024/2025 academic year. The method used in this research uses quantitative with a descriptive approach to inferential statistics. The population is all class IX students of SMP Negeri 4 Doloksanggul, Humbang Hasundutan Regency for the 2024/2025 academic year, totaling 149 people and a sample of 43 people was determined, namely 30% of the population using simple random sampling techniques. Data was collected using a positive closed questionnaire with 46 items. The results of data analysis show that there is a positive and significant influence of Game Based Learning by PAK teachers on the interest in learning PAK of class IX students of SMP N 4 Doloksanggul for the 2024/2025 academic year: 1) Test the analysis requirements: a) a positive relationship test obtained a value of rxy = 0.594> rtable = 0.301, thus it is known that there is a positive relationship between variable significant between variable b) Regression coefficient of determination test (r2) = 35.3%. 3) Testing the hypothesis using the F test obtained Fcount> Ftable=22.28>1.51. Thus Ha is that there is a positive and significant influence of Game Based Learning by PAK teachers on the interest in learning PAK of class IX SMP N 4 Doloksanggul Academic Year 2024/2025 is accepted and H0 is rejected.